ANALISIS PENGARUH IMPLEMENTASI BUDAYA ORGANISASI, KOMPETENSI DAN SERTIFIKASI GURU TERHADAP KINERJA GURU - Hatemu Hatemu (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This research is organizational culture, competence and teacher certification and teacher performance in Pulau Rimau. The sample in this study amounted to 34 rayon teachers 1 Rimau Island Sub-district. Data analysis in this research is multiple linear regression with the help of SPSS For Windows program. Based on the data analysis stated that if there is an increase of organizational culture, competence and certification then the performance of teachers will increase. Organizational culture shows improvement of teacher performance while competence variable with teacher certification does not show improvement of teacher performance.